Efficient Acquisition of Fully Human Antibody Genes against Self-Proteins by Sorting Single B Cells Stimulated with Vaccines Based on Nitrated T Helper Cell Epitopes - Jiang, Liangliang; Jiang, Tao; Luo, Jianhua; Kang, Yanliang; Tong, Yue; Song, Xiaoda; Gao, Xiangdong; Yao, Wenbing; Tian, Hong (Journal of Immunology Research, 2019)
Single B cell antibody technology is a method for isolating antigen-specific B cells from human peripheral blood and obtaining antibody genes in developing antibody drugs. However, owing to immune tolerance to autoantigen, human autoantigen-specific B cells are difficult to acquire by conventional single B cell technology. In this study, we constructed a nitrated T-cell epitope named NitraTh by incorporating p-nitrophenylalanine into a universal T helper epitope. NitraTh had enhanced ability to activate CD4+ T cells and can be recognized by CD4+ T cells with different HLA class II haplotypes. This NitraTh can also break immune tolerance to autoantigens, such as human epidermal growth factor receptor 2 (HER2) and cannabinoid receptor 1, and induce strong specific IgM+ B cell responses in vitro. HER2-NitraTh vaccine can also stimulate the generation of HER2-specific IgG+ B cells in human immune system mice, which was established by cotransplanting lymphocytes and autologous dendritic cells in immunodeficient mice. We obtained 30 fully human IgG antibody genes by sorting single B cells from the human immune system mice immunized with HER2-NitraTh vaccine. The analysis of antibody genes showed that sorted B cells underwent the extensive somatic mutation of the antibody genes. We randomly selected eight genes for cloning, six of which expressed antibodies that can bind to HER2. Hence, we provided a convenient and effective method in acquiring fully human antibody genes against self-proteins, which can be used in developing therapeutic antibody drugs.